Attitude development through students learning activism - Chinnasamy, K.; Muthumari, P.; Aravind, S. (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
This case study focuses on attitude development of student’s to challenge learning activism for gender individuals in higher education. There is a hope that this study will stimulate further in depth studies which may help to improve the learning habit and to develop the attitude among the college students. This research is mainly based on primary data which has been collected through a well-structured questionnaire. The questionnaire has been distributed in Postgraduate Students and collected to 374 respondents on different locations of college in Madurai District, Tamilnadu, India. Using participant observation deliberate and lists previously studied constraints from existing literature.